(3WHbGJ CUMGH ehdGfG CHj MGeO GdYQHj Hf CMeO GdOQbGhj GdMSfjs - (3CHh RjGf Hf CMeO GdZQjSj GdeYScQ GdOQbGhj,J (B1271 (3g` s
(3ChdgG (B:s
(3hHYO , abO CQOJ Cf CbjO haGI CSJGPi hedGPi GdTQja GdOQbGhj eY VYaj hbUQ HGYj s
(3BNQgG (B:s
(3aeWQM GdCLdI bHdI ef CTjGNfG GdaGSjjf hGdjefjjf QVi Gddg Yfge CLeYjf s
(3aj U (B176 (3fSNI CNQi ef GdcJGH HGSe WHbGJ GdUhajI aj GdbQf GdKGdK YTQ GdgLQi HQbe (B6502(3Ms
(3GdJhKjbGJ GdeQLYjI (B:s
(3Odjd eDQN GdeZQH (B- (3U (B305 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B268 ; (3agQS OGQ GdcJH GdeUQjI (B- (3GdLRA (B8 - (3U (B150 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B4759) s
Keywords: (3GdJGQjNs